2013
DOI: 10.1136/archdischild-2012-303482
|View full text |Cite
|
Sign up to set email alerts
|

Pain in young people aged 13 to 17 years with cerebral palsy: cross-sectional, multicentre European study

Abstract: ObjectiveTo determine the prevalence and associations of self- and parent-reported pain in young people with cerebral palsy (CP).Design and settingCross-sectional questionnaire survey conducted at home visits in nine regions in seven European countries. Participants were 13 to 17-year-olds (n=667) drawn from population CP registers in eight regions and from multiple sources in one region. 429 could self-report; parent-reports were obtained for 657. Data were collected on: severity, frequency, site and circumst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
204
7
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(241 citation statements)
references
References 32 publications
27
204
7
3
Order By: Relevance
“…Previous multicenter studies have shown the prevalence of pain in the CP population to be 75-80% 26,27 which is similar to the prevalence of 87% in CP patients with spasticity found in the current study. Likewise, our data in patients with spasticity concurs with previous studies that reported prevalence of pain in stroke to be 19-75%, [26][27][28] 53% in MS, 29 64.9% in SCI 30 and 70% in brain injured patients.…”
Section: Discussionsupporting
confidence: 90%
“…Previous multicenter studies have shown the prevalence of pain in the CP population to be 75-80% 26,27 which is similar to the prevalence of 87% in CP patients with spasticity found in the current study. Likewise, our data in patients with spasticity concurs with previous studies that reported prevalence of pain in stroke to be 19-75%, [26][27][28] 53% in MS, 29 64.9% in SCI 30 and 70% in brain injured patients.…”
Section: Discussionsupporting
confidence: 90%
“…Although this level was high, it was still lower than the 50‐75% reported by other CP studies 4, 6, 8, 9, 15. A number of explanations can account for this apparent discrepancy.…”
Section: Discussionmentioning
confidence: 57%
“…Some of the other studies focused on specific types of pain, such as musculoskeletal pain 8, or included specific subtypes of CP, for example bilateral spastic 16, both of which could influence the prevalence rate. Furthermore, we included a wide age span, one to 14 years of age, whereas the other studies focused more on pain in adolescents with CP 6. Our results did indicate that pain prevalence increased with age.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations